Phytoplankton diversity as a bioindicator for water quality of Tanjung Aan, SEZ Mandalika Central Lombok - Tisanianti Tisanianti; Dining Aidil Candri; Lalu Japa (Jurnal Pijar Mipa, 2023)
Coastal waters of the Special Economic Zone (SEZ) Mandalika must be given more attention as it is the centre of tourism activities, including the International GP motor circuit on the island of Lombok. One of the bioindicators used in determining water quality is phytoplankton. Phytoplankton is tiny organisms that float on the water, have very weak swimming abilities, and their movements are heavily influenced by water flow. This research aimed to determine the diversity of phytoplankton as a bioindicator in the waters of Tanjung Aan, Central Lombok. Sampling sites in Tanjung Aan were determined by purposive sampling. This research was conducted from March to June 2023. The research results showed that there were six classes, 56 families, and 56 genera with 128 species in the community of phytoplankton. Species 113 were members of the class Bacillariophyceae. The phytoplankton abundance in three sampling sites ranged from 488 ind/L to 1109 ind/L. The species diversity indexes of phytoplankton in the three sampling sites ranged from 2.4 to 2.9, which means that the diversity is in the low category, and the species dominance index ranges from 0.12 to 0.15. This indicates that the condition of the waters of Tanjung Aan is slightly polluted.